Uprobe: A genome-wide universal probe resource for comparative physical mapping in vertebrates - Kellner, Wendy A.; Sullivan, Robert T.; Carlson, Brian H.; Thomas, James W. (Genome Research, 2005)
Interspecies comparisons are important for deciphering the functional content and evolution of genomes. The expansive array of >70 public vertebrate genomic bacterial artificial chromosome (BAC) libraries can provide a means of comparative mapping, sequencing, and functional analysis of targeted chromosomal segments that is independent and complementary to whole-genome sequencing. However, at the present time, no complementary resource exists for the efficient targeted physical mapping of the majority of these BAC libraries. Universal overgo-hybridization probes, designed from regions of sequenced genomes that are highly conserved between species, have been demonstrated to be an effective resource for the isolation of orthologous regions from multiple BAC libraries in parallel. Here we report the application of the universal probe design principal across entire genomes, and the subsequent creation of a complementary probe resource, Uprobe, for screening vertebrate BAC libraries. Uprobe currently consists of whole-genome sets of universal overgo-hybridization probes designed for screening mammalian or avian/reptilian libraries. Retrospective analysis, experimental validation of the probe design process on a panel of representative BAC libraries, and estimates of probe coverage across the genome indicate that the majority of all eutherian and avian/reptilian genes or regions of interest can be isolated using Uprobe. Future implementation of the universal probe design strategy will be used to create an expanded number of whole-genome probe sets that will encompass all vertebrate genomes.